2022
DOI: 10.18502/ijm.v14i1.8794
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of gut microbiota in patients with COVID-19, its relationship with lung axis, central nervous system (CNS) axis, and improvement with probiotic therapy

Abstract: Coronavirus Disease 2019 (COVID-19) is a pandemic disease caused by a new corona virus. COVID-19 affects different people in different ways. COVID-19 could affect the gastrointestinal system via gut microbiota impairment. Gut microbiota could affect lung health through a relationship between gut and lung microbiota, which is named gut-lung axis. Gut microbi- ota impairment plays a role in pathogenesis of various pulmonary disease states, so GI diseases were found to be associated with respiratory diseases. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 90 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Recent publications have suggested that disruption of the microbiota and impairments in intestinal barrier function triggers local inflammation by activating the immune system and causing severe COVID-19 infections on the gut–lung–brain axis in adults [ 154 , 155 ] and likely in children diagnosed with MIS-C. GI dysfunction in MIS-C is under ongoing investigation [ 156 , 157 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent publications have suggested that disruption of the microbiota and impairments in intestinal barrier function triggers local inflammation by activating the immune system and causing severe COVID-19 infections on the gut–lung–brain axis in adults [ 154 , 155 ] and likely in children diagnosed with MIS-C. GI dysfunction in MIS-C is under ongoing investigation [ 156 , 157 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences between children and adults in connection with the previously mentioned gastrointestinal implications of COVID-19 are depicted in Figure 1. [154,155] and likely in children diagnosed with MIS-C. GI dysfunction in MIS-C is under ongoing investigation [156,157].…”
Section: Discussionmentioning
confidence: 99%
“…5,6,9 In the gastrointestinal tract, the gut-lung axis has been described as responsible for damage to the intestinal mucosa, possibly conferring an increased risk of inflammatory bowel disease and chronic liver disease, as well as increased injury at the pulmonary level due to modification of the immune response by producing an unhealthy gut microbiome. [20][21][22] The probable destruction of the β-cells of the islets of Langerhans in the pancreas may trigger insulin-dependent diabetes mellitus and further increase morbidity and mortality in patients. 6,23,24 In the central nervous system, systemic inflammation and entry of the virus through ACE-2 receptors expressed in the brain are probably responsible for a decrease in cognitive capacity, memory loss, fatigue, and neurogenic hypertension.…”
Section: Probable Sequelae Of the Infectionmentioning
confidence: 99%
“…Experimental studies have shown that the absence of a healthy intestinal microbiome generates consequences in the preservation of the immune system, avoiding exaggerated or deficient responses to pathogens that can be harmful to other organs such as the lungs (gut-lung axis). [20][21][22] Páncreas -Islets of Langerhans. ACE-2 expression has been shown to be higher in islets of Langerhans (site of insulin production) and lower in exocrine cells.…”
Section: Table 1 Tissues Where Ace-2 Receptor Is Expressed and The Pa...mentioning
confidence: 99%